An OPNET simulation model for peer-to-peer networks. (August 2013) - Hawa, Mohammed
Peer-to-peer (P2P) traffic has increased rapidly over the past few years, with file sharing providing the main drive behind such traffic. Therefore, modeling P2P systems and studying their impact on the performance of the underlying network is a vital research topic. In this work we describe a flexible, efficient and easily expandable P2P simulation framework developed for the OPNET simulation package. The framework can be used to study a wide variety of issues regarding the packet-level and/or the flow-level performance of P2P systems, including the impact of cooperation incentives on file dissemination; mobility and quality of service (QoS) support in P2P distribution; and the effects of free-riding, resource pollution, and malicious attacks on P2P networks.